1996
DOI: 10.1002/j.1550-8528.1996.tb00513.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Maternal Psychopathology and Family Socioeconomic Status with Psychological Problems in Obese Children

Abstract: EPSTEIN, LEONARD H, MICHELLE D MYERS,KATARINA ANDERSON. The association of maternal psychopathology and family socioeconomic status with psychological problems in obese children. Obes Res, 1996;4:65-74. In an earlier study we found parental psychiatric symptoms to be a better correlate of behavioral problems in obese children than either child or parental obesity. This study sought to extend this research by assessing the association of general maternal distress, specific maternal psychopathology, family socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
3
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 47 publications
8
54
3
3
Order By: Relevance
“…A pilot study by Epstein et al 2 suggested that, apart from parental obesity, parental psychiatric symptoms are much more related to the child's psychological problems than the child's overweight. These results were replicated by Epstein et al 6 for maternal distress. Recently, Zeller et al 7 confirmed and elaborated these findings in children as well as in adolescents, seeking treatment at an outpatient pediatric weight control clinic by collecting data from different informants.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…A pilot study by Epstein et al 2 suggested that, apart from parental obesity, parental psychiatric symptoms are much more related to the child's psychological problems than the child's overweight. These results were replicated by Epstein et al 6 for maternal distress. Recently, Zeller et al 7 confirmed and elaborated these findings in children as well as in adolescents, seeking treatment at an outpatient pediatric weight control clinic by collecting data from different informants.…”
Section: Introductionsupporting
confidence: 66%
“…31,32 Moreover, using the same cutoffs for the CBCL as Epstein et al 6 and according to gender, between 41.4 and 53.1% of the youngsters seeking weight-loss treatment showed considerable adjustment problems, whereas their parents scored higher than a representative norm group on psychiatric symptoms. Compared with the study of Epstein et al, 6 the present study even found a larger percentage of parents exceeding clinical cutoffs for psychiatric symptoms (59.6% of mothers and 35.7% of fathers) than Epstein et al 6 (27.6% of mothers). However, children in this study were older and not enrolled in a treatment research trial.…”
Section: Parent Characteristics and Psychopathology In Obesity V Decamentioning
confidence: 92%
See 1 more Smart Citation
“…Convém salientar que esse dado é compatível com a literatura, que aponta que problemas comportamentais são encontrados, com maior frequência, entre as crianças obesas, quando avaliadas pelos pais ou professores (Epstein et al, 1996;Stradmeijer et al, 2000). Esses resultados evidenciam a necessidade de implementar estratégias específicas de tratamento, como o atendimento psicológico a essas crianças, enfocando a diminuição de tais problemas, e orientações específicas aos pais, com o objetivo de ensinar estratégias adequadas para lidarem com os filhos.…”
Section: Discussionunclassified
“…Among those are the child's referral status, gender and age, degree of overweight, socio-economic status (SES), level of physical activity, parental psychological adjustment and last but not least level of teasing and social rejection. In general, the trends emerging from both clinical and community studies are that children seeking treatment, children who are older and girls in particular, 1 children with lower SES, 2,9 children who have parents who report worse psychological adjustment for themselves 2,[9][10][11][12][13] and children who report experiencing teasing or social rejection [14][15][16] seem to be at risk for higher rates of psychological adjustment than those who do not report experiencing teasing or social rejection. However, a higher degree of overweight has not been associated with an increased risk of psychological maladjustment in clinical samples of obese children, 2,9-11 although this association has been commonly observed among community-based samples.…”
Section: Introductionmentioning
confidence: 99%